(untitled) (IDENTITĂȚI COLECTIVE ȘI IDENTITATE NAȚIONALĂ. PERCEPȚII ASUPRA IDENTITĂȚII ÎN LUMEA MEDIEVALĂ ȘI MODERNĂ. ln memoriam Alexandru Duţu, 2026)
Eastern Europe has recently been an arena for a spectacular revival of various nationalisms, often in conflict with one another, but similar in structure and forms of expression. Challenging all theories and scenarios which postulated the gradual and rather smooth establishment of supranational organization schemes, either at world level or at European level (be it in the elitist and limited pattern of the European Economic Community, or in the enlarged version of the European Common House suggested by Mikhail Gorbachev), this phenomenon needs the full attention of social scientists.